Teachers' Perspectives on CIM at Elementary Schools - Darmawan, Deni; Ihsan Basyori, Sansan; Koswara, Ucu; Jam Jamilah, Jam; Rohmatul Illahi, Padmi (Green Publisher Indonesia, 2024)
This study aims to find out the extent of teachers' perspectives or views on: (1) Learning using ICT as a learning medium or tool, (2) Interactive Multimedia Learning. Based on Canva application can increase students' motivation to learn and, (3) Fun Interactive Multimedia Learning. The research method used by the researcher in this study is a descriptive research method with a quantitative approach. The research was carried out on elementary school (SD) teachers in Bungbulang district, Garut regency. The subject of this study is elementary school teachers with a sample of 75 respondents from all teachers in elementary schools as many as 300 people. In collecting data from the samples taken using a questionnaire or questionnaire technique with the scale used, namely the Likert scale. The results of this study, namely that the teacher's perspective on ICT learning as a medium or learning tool is highly expected and this can be seen from the results of the data analysis collected, namely 36 (48%) respondents answered strongly agree, and 28 (37%) respondents answered yes. This means that respondents agree to ICT-based learning. The conclusion to the perspective of CIM (Canva Interactive Multimedia) is also very significant that 36 (48%) respondents agree and 25 (33%) respondents strongly agree with the learning process using CIM. And finally, as many as 39 (52%) respondents answered yes and 21 (28%) respondents answered strongly agree. This means that the existence of CIM in learning will provide results, namely it will increase interest in learning and be fun. Broadly speaking, the teacher's perspective on CIM provides a positive view that can increase students' motivation in the learning process.